Cuestiones sociojurídicas con enfoque de género : una perspectiva desde los semilleros de investigación - Pattaro Amaral, Fernanda (Corporación Universitaria Americana, 2023)
This publication proposes a series of analyses with a gender approach from different debates: historical, doctrinal, jurisprudential, epistemological, legal, methodological and empirical. The reference to the "gender approach" consists of the forms of inequality existing in society between men/women and LGBTIQ+ groups, which considers that one sex (biological - binarism - domination - theory of biological essentialism) must be inferior to the other.